Authentic materials for developing listening comprehension - Azizah Azizah (Universitas Syiah Kuala, 2016)
This study was designed to investigate the effects of the use of authentic materials in teaching listening to the English Department students of UIN Ar-Raniry, Banda Aceh. The purpose was to find out whether students who got authentic materials in their listening class would get a better result compared to those who did not. The population of this study was all the second semester students who took Listening 2; then two classes were selected using random sampling as the samples; the experimental class (EG) with 25 students and control class (CG) with 27 students. Data was collected quantitatively from the results of the pre-tests and the post-tests of listening while qualitative data was obtained from the questionnaire distributed at the end of teaching to identify the EG students’ perceptions of the use of authentic materials in listening. The findings showed that the mean post–test score from the EG at 82 was higher than that from the CG at 71, which according to the results from the t-test was significantly higher. This meant that the students who were taught using authentic materials get a significantly better result in listening than those who were taught using the usual course book materials. The responses in the questionnaires showed that the students prefered the authentic listening materials for learning listening skills as these materials were more interesting and more related to their real life context so that it motivated them to pay more attention in the listening class and this also assisted them to improve their listening abilities.